New perspectives on management of idiopathic pulmonary fibrosis - Puglisi, Silvia (Ther Adv Chronic Dis, 2016)
Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive parenchymal lung disease characterized by a median survival of 3–5 years following diagnosis. The diagnosis is based on clinical, radiological and histopathological evaluation. Therefore, a multidisciplinary team is needed to reach the correct diagnosis. For a long time, supportive care and lung transplantation in selected cases, have been considered the only possible treatments for IPF. In the last decade many studies have investigated IPF pathogenesis, leading to an improved knowledge of the mechanisms underlying the disease and to the approval of two new drugs for IPF treatment (pirfenidone and nintedanib). The therapeutic approach of IPF cannot be limited to the administration of antifibrotic drugs, but it is necessary for improving the quality of life of patients and for facilitating, as far as possible, the performance of normal daily activities and relationships. IPF patients are also afflicted by disease-related complications such as gastroesophageal reflux, pulmonary hypertension, acute exacerbations and an increased risk of developing lung cancer. The clinician who treats IPF patients, should also treat these possible complications to slow disease progression, thus maintaining the possibility of a pulmonary transplantation.